Point mutations in the herpes simplex virus type 1 Vmw110 RING finger helix affect activation of gene expression, viral growth, and interaction with PML-containing nuclear structures. - Everett, R (1995)
Herpes simplex virus type 1 immediate-early protein Vmw110 (also known as ICP0) has been implicated in the control of the balance between the lytic and latent states, but the precise mechanisms by which it exerts its effects are unknown. Vmw110 includes a characteristic zinc binding domain, termed the C3HC4 domain or RING finger, which is essential for its function. The solution structure of a related herpesvirus RING finger domain suggested that an amphipathic alpha helix might be an important functional component of the RING finger. In this paper, we show that the equivalent region of Vmw110 is important for virus growth in tissue culture and for the normal interaction of Vmw110 with nuclear structures which include the PML protein.